Study on the Workspace and Kinematics of 3-UPU Parallel Mechanism - Pu Zhixin; Li Xiaochun; You Xuping; Yu Yinghua (Jixie chuandong)
According to the structural characteristic of 3- UPU parallel mechanism,by using a new numerical algorithm,the kinematics inverse solution of the mechanism is obtained. Through the compound derivation for the mechanism kinematics inverse solution,the Jacobi matrix of the mechanism kinematics is fast obtained. And the singularity analysis of mechanism is carried out,the three cases of singular configuration are obtained. At last,by using the limit search method combined with MATLAB software,the workspace of mechanism is obtained. A theoretical foundation for the study on the parallel mechanism parameters optimization is provided.